Impervious Surface Mapping of Kathmandu Metropolitan City (OODBODHAN, 2026)
Rapid urbanization all around the world has brought about a massive proliferation of impervious surfaces. Even the capital, the economic hub of Nepal, Kathmandu Metropolitan has not been spared from proliferation of impervious surface. Impervious surface has adverse effect on ground water table as they prevent water from permeating through them and refilling the underground table. So, it is imperative to identify and map these surface so as to aid in urban planning. This study aims to create impervious map of Kathmandu Metropolitan city using thresholding method utilizing the threshold values developed by different studies and develop three different models utilizing the combination of bands, specific indices and all the indices used for this study. Out of the 3 models created, the model that utilized 7 different indices along with the spectral bands of Sentinel, performed the best in detecting the impervious surface indicating the fact that use of indices indeed can help in identification of built-up areas better due to their respective properties in terms of reflectance. This study provides foundation for future studies relating impervious surface to urban management and underground water table studies as well.